Numerical investigation of the transient interfacial material behavior during laser impact welding. (1st February 2022) - Gleason, Glenn; Sunny, Sumair; Mathews, Ritin; Malik, Arif
Graphical abstract: Abstract: During laser impact welding, severe plastic strains and temperature spikes occurring in less than 1 µs make experimental observation impractical and necessitate computational modeling to characterize in-situ behavior. To understand the effects of microstructure and the associated inhomogeneity/anisotropy in laser impact welding, an Eulerian framework featuring aluminum 1100 flyer and stainless steel 304 target foils is applied to simulate cases with and without microstructure modeling. The transient thermomechanical phenomena revealed by the dynamic simulation provide insights into evolution of the in-situ structure-property relationship, including microstructural variation, phase transformation, and material jetting. In contrast to the homogeneous model, the inhomogeneous model suggests a 10 µm-thick zone of grain refinement at the weld interface establishing new grains 0.1-1 µm in diameter in the flyer, and causing partial martensitic phase transformation in the target, attributable to rapidly induced equivalent plastic strains of up to 10.71 in the flyer and 0.98 in the target.